Comparison of polyaluminum silicate chloride and electrocoagulation process, in natural organic matter removal from surface water in ghochan, Iran - Mahvi, A.H.; Malakootian, M.; Heidari, M.R. (Химия и технология воды, 2011)
Removal of Natural Organic Matter (NOM)is one of the most important objectives of water treatment plants but reducing these pollutants either present in water as dissolved or suspended form is not as efficient as is required in conventional treatment plants. The purpose of this study was comparison performance of composite polyaluminum silicate chloride (PASiC) and electrocoagulation (EC) process by aluminum electrodes in NOM removal from raw surface water. Удаление природных органических веществ (ПОВ) является одной из наиболее важных задач при очистке поверхностных вод. Однако удаление ПОВ, находящихся в растворенной форме или в виде суспензий, не настолько эффективно, как это требуется при работе водоочистных сооружений. Изучено влияние мутности, общего органического углерода (ООУ), адсорбции ПОВ при длине волны 254 нм (УФ254 нм), ХПК, щелочности в процессе электрокоагуляции и при использовании композитного четыреххлористого кремния полиалюминия (КЧКП). Видалення природних органічних речовин (ПОР) є одним з найбільш важливих завдань при очищенні поверхневих вод. Проте видалення ПОР, що знаходяться в розчиненій формі або у вигляді суспензій, не настільки ефективно, як це потрібно при роботі водоочисних споруд. Вивчений вплив каламутності, загального органічного вуглецю (ЗОУ), адсорбції ПОР при довжині хвилі 254 нм (УФ254 нм), ХПК, лужності в процесі електрокоагуляції і при використанні композитного чотирьоххлорістого кремнію поліалюмінію (КЧКП).